Method Development and Validation of Olmesartan Medoxomil by Using RP-HPLC - Kushwaha, Anchal; Nagarajan, Kandasamy; Goel, Richa; Kapoor, Garima; Bhardwaj, Snigdha; Bhatt, Pankaj (International Journal of Pharmaceutical Investigation, 2025)
Background Olmesartan (OLM) is a drug used to treat hypertension, or elevated blood pressure. Controlling high blood pressure lowers the chance of further strokes, renal problems and heart attacks. Materials and Methods The article presents a comprehensive overview of the drug’s pharmacological characteristics and therapeutic effectiveness. A UV spectrophotometric technique was used to determine the solubility of Olmesartan medoxomil in a range of solvent ratios, including ethanol, methanol, acetonitrile, chloroform, pyridine, acetone, ethyl ether and distilled water. This was carried out since parameter analysis, drug validation and HPLC technique development all heavily depend on the solubility of the drug. The dissolution rates of several compounds were measured in a number of solvents, including distilled water, ethanol, methanol, acetonitrile, acetone, chloroform and pyridine. For every solvent, the UV spectra were measured between 200 and 400 nm. The λmax values for several solvents were analyzed and recorded. Results and Discussion The study revealed that Olmesartan medoxomil is very soluble in methanol and ethanol. A wavelength of 256 nm for methanol and an absorbance of 0.291 were used. The C18 (4.6×250 mm, 5 µ) particle size column in our approach was filled with water (containing 5% ammonium acetate) and methanol (5%:95%) at room temperature and 1.0/min flow rate using 10-min runtime. Olmesartan medoxomil eluted with a retention time of exactly 2.3 min. Conclusion Using 10 min runtime, Olmesartan medoxomil eluted with a retention time of exactly 2.3 min.
Keywords: Olmesartan medoxomil; Hypertension; Validation; RP-HPLC